Global Map of Martian Fluvial Systems: Age and Total Eroded Volume Estimations. Issue 10 (3rd October 2018) - Alemanno, G.; Orofino, V.; Mancarella, F.
Abstract: The study of the fluvial systems present on the Martian surface is a key in the investigation of the paleoclimate of the planet: Various indications suggest that these features could have formed under climatic conditions very different from the present one. For this reason, it seems necessary to update the previous maps of Martian valleys using newer mosaics and data at higher resolution. In this work we present a detailed global map of Martian valleys classified according to their morphology. Our data set includes all the valleys longer than 20 km mapped within the QGIS (Quantum Geographic Information System) software. With respect to previous global maps, the coupling of topographic information with data of higher image quality allowed us a better mapping of these structures at a fine scale: New small valleys and more tributaries for several systems have been observed. We mapped valleys of various typologies for a global total length of 773, 559 km. The mapped valley networks cover the 69% of this total length. Moreover, a rough estimation of the valleys' age spatial distribution was performed. We found that the 94% of the mapped valleys have a maximum age consistent with an origin in the Noachian period; the 4% have a Hesperian maximum age, while the remaining 2% have a maximum age consistent with an origin in the Amazonian period. Finally, we also estimated the total eroded volume of the mapped valley networks finding a value in the order of 3 × 10 14 m 3 in good agreement with what found in literature. Key Points: The widespread fluvial structures on Mars are an indication of the ancient presence of liquid water on its surface To further constraint the ancient climate of the planet we updated previous global maps of Martian fluvial structures Age and volume estimations of the mapped valleys were made on the basis of the data obtained